PENYULUHAN DAN PEMBINAAN PENINGKATAN SEMANGAT NASIONALISME PADA GENERASI MUDA DI DESA BADERAN KECAMATAN GENENG KABUPATEN NGAWI - Endang Murti; Retno Iswati; Isni Wahidiyah Susanto; Agus Wiyaka (Universitas Merdeka Madiun, 2023)
The expected output targets are as follows: (1) Fostering national insight to the younger generation; (2) Conducting outreach the importance of the spirit of nationalism in counteracting the negative impacts of globalization; and (3) Organizing training to increase spirit of nationalism among the younger generation. Planned activities will be implemented using methods that include (1) Conseling regarding increasing the spirit of nationalism, broadening national insight and the impact of globalization on national and state life; (2) Training to enforce discipline and foster a spirit of nationalism, (3) Participation of partners in implementing this program activities includes: planning schedules and places for counseling and training activities, providing materials and props for training, providing time and energy during implementing programs and helping to seek sustainable collaboration in the context of coaching and training the younger generation. After carrying out this community service, the results of the activities can be concluded as follows: (1) The spirit of nationalism young generation who are members of the Baderan Village Youth Organization, Geneng District, Ngawi Regency has increased; (2) Increasing national insight in the younger generation; and (3) The younger generation can avoid the negative impacts of globalization of technology and information in the life.